Estrategia psicopedagógica para mejorar la convivencia escolar en los estudiantes de 8vo año de la unidad educativa José María Velasco Ibarra. - Solorzano Zambrano , Evelyn Siharet (2025)
The research aimed to design a psychopedagogical strategy to improve school coexistence among eighth-grade students of Basic General Education at the "José María Velasco Ibarra" Educational Unit, considering that coexistence represents an essential factor for comprehensive development, learning, and socio-emotional well-being. The general objective was to develop a contextualized psychopedagogical proposal that would respond to the problems identified in the institutional diagnosis, which revealed interpersonal conflicts, communication difficulties, limited empathy, and weak emotional self-regulation. The study was conducted using a mixed approach with a predominantly qualitative, descriptive-propositional approach, with a non-experimental and cross-sectional design. Semi-structured interviews, participant observation, documentary analysis, and the administration of the CES questionnaire were used, which allowed for triangulation of information and guaranteed the validity of the findings. The results showed that students' school coexistence was sustained by social cohesion and regulatory clarity, but presented weaknesses in intrinsic motivation, active participation, and openness to change, which limited the school climate and comprehensive development. In addition, a theoretical and empirical analysis was conducted, which supported the design of a strategy based on constructivism, social learning, emotional education, and psychopedagogical mediation, complemented by restorative practices. The strategy was validated through expert judgment without ever being applied in the field. It was concluded that the proposal constituted a viable and applicable alternative in similar educational contexts, with the potential to strengthen emotional self-regulation, group cohesion, and peaceful conflict resolution, fostering an inclusive and democratic environment. However, its implementation was postponed for future educational processes.